Can threshold for MPO by flow cytometry be reduced in classifying acute leukaemia? A comparison of flow cytometric and cytochemical myeloperoxidase using different flow cytometric cut-offs. Issue 8 (September 2015) - Manivannan, Prabhu; Puri, Vandana; Somasundaram, Venkatesan; Purohit, Abhishek; Sharma, Rahul Kumar; Dabas, Mandeep; Saxena, Renu
<x content-type="archive" xml:space="preserve">Abstract</x> Objectives Myeloperoxidase (MPO) detection either by enzyme cytochemistry (cMPO) or flow cytometry (fMPO) plays a major role in acute leukaemia (AL) diagnosis as per World Health Organization (WHO) 2008 classification. Although 3% cMPO was recommended as positivity, no specific cut-off had been mentioned by WHO for fMPO. Various authors recommend different cut-offs ranging from 3 to 28% for fMPO. The aim of this study was to analyse fMPO cut-offs ranging from 3 to 10% in classifying AL and to assess whether a new cut-off could be suggested. Methods Totally, 216 cases of AL were retrospectively analysed for fMPO ranging from 3 to 10% and compared with gold standard. Presence of cMPO (≥3%) and/or expression of two or more pan-myeloid markers (CD13, CD33, and CD117) in the absence of CD19 and CD3 were kept as gold standard for diagnosis of acute myeloid leukaemia (AML). Results Sensitivities for classifying AL as AML/mixed phenotypic acute leukaemia (MPAL) at 3, 5.4, and 10% were 98.3, 98.3, and 96.6%, respectively, whereas specificities at this cut-off were 22.2, 91, and 71%, respectively. Discussion Only few studies have been done in this aspect to define a consistent cut-off for fMPO for proper classification of acute leukaemias. This was one of the largest and few studies available till date in this regard. Conclusion The newer cut-off for fMPO (5.4%) emerged out from our study with best sensitivity and specificity for accurately classifying AL cases into acute lymphoblastic leukaemia, AML, and MPAL.